Study of radiative characteristics of a completed partial discharge - Yakovlev, E.A.; Yugay, V.V.; Zinovyev, L.A.; Kashlev, A.R.; Bezrukov, V.O. (Journal of Physics: Conference Series, 2021)
The work is devoted to the study of the optical and electrical characteristics of a completed partial discharge burning in the presence of an electrolyte (1.5% NaCl solution). The possibility of using optical sensors that are part of smartphones such as Xiaomi for research is shown. The dependence of the radiation intensity of the completed partial discharge on the value of the ballast resistance in the discharge circuit and the material of the grounded electrode (anode) is studied. The dependence of the breakdown voltage on the size of the discharge gap is also studied. It is shown that it has a nonlinear character at a significantly lower (up to 20 times) breakdown voltage in comparison with the case of the absence of an electrolyte.